Toxicity profiling of liposome encapsulated chlorogenic acid formulation in zebrafish embryos at different developmental stages - D.SIVARAMAN, (International Journal of Pharma and Bio Sciences, 2018)
Regulatory authorities globally alarming about the growing concern on threatening exposure of several chemicals and carcinogens due to its tendency to cause developmental and reproductive abnormalities. Hence it’s a right time to explore novel analytical strategy for evaluating such potential agents in suitable in-vivo system. Further the data’s of such investigation can be precisely extrapolated to human toxicities. Zebrafish (Danio rerio) attains greater importance in the field reproductive biology due to its close genetical resemblance with respect to that of the humans. The main aim of the present investigation is to carry out the toxicity profiling of the Liposomal encapsulated chlorogenic acid (LipoCA) in Zebrafish embryos. LipoCA formulated using thin-layer evaporation method and it was exposed to healthy embryos at the concentration ranging from 10µg to 640µg/ml. The data obtained from the present investigation reveals that there is no significant difference in heart rate of the drugs treated groups (124.3 ± 2.60 to 127.7 ±4.87) with that of the control embryos (125.2 ± 2.16 beats/min). Further there was no significant difference in movement analysis of the drugs treated groups (7.83 ± 1.31 to 8.6 ± 1.67 per min) with that of the control embryos (7.96 ± 1.52 per min). Further there was no abnormalities were detected in observed parameters such as hatching rate, blood circulation, pigmentation, swimming pattern, balancing and morphogenesis. It was concluded from the results of the present investigation that LipoCA was safe and didn’t alter any of the physiology of the developing fetus upon 24 to 96 hours post fertilization (HPF).